Extraction, characterization and antioxidant activity of polysaccharide from Pouteria campechiana seed. (1st February 2020) - Ma, Jin-Shuang; Liu, Hong; Han, Chang-Ri; Zeng, Si-Jie; Xu, Xiao-Jun; Lu, Deng-Jun; He, Hong-Ju
Highlights: Optimization extraction of polysaccharide from Pouteria campechiana seeds by RSM. PCSPa-1 is a high molecular weight polysaccharide with a glucose structure. The anti-DPPH radicals activity of the PCSPa-1 sample was comparable to that of Vc. Abstract: In this study, the seed polysaccharides (PCSP) was ultrasonic-assisted extracted from Pouteria campechiana and optimized by response surface method (RSM). After separation and purification by DEAE-52 cellulose column and Sephadex G-75 glucan gel column, the pure polysaccharide component of PCSPa-1 was obtained, and its structure and antioxidant activity were analyzed. The results showed that the optimal parameters of PCSP with maximum yields (15.94%) were ultrasonic temperature of 79 °C, ultrasonic time of 69 min, and liquid to material ratio of 41 mL/g. The molecular weight of PCSPa-1 was 67900 Da. PCSPa-1 consisted of glucose and mannose with a molar ratio of 86.65:4.62, and the glycosidic bond mainly included →4)-α-d -Glc(1→ and →6)-α-d -Glc(1→. Scanning electron microscopy showed that PCSPa-1 was a strip structure with a smooth surface. In addition, PCSPa-1 had strong scavenging capacity to 1, 1-diphenyl-2-picrylhydrazyl (DPPH), 2, 2 ' -azino-bis- (3-ethylbenzthiaz oline-6-sulphonic acid) (ABTS), hydroxyl radical, and superoxide radical. Polysaccharides of Pouteria campechiana seeds could be exploited as a natural antioxidant.